The epigraphy of an islamic mould in Lorca (Murcia) - Sánchez Gallego, Rubén; Espinar Moreno, Manuel (Anaquel de Estudios Árabes, 2006)
In this paper we study the epigraphic characteristics of a series of amulets and talismans conserved in a mold obtained in an archaeological excavation in Lorca (Murcia). Their epigraphy and symbolism are emphasized in this study. They are compared with other archaeological pieces in the literature.